Probiotic effects on cobia Rachycentron canadum larvae reared in a recirculating aquaculture system - M. Angélica Garrido-Pereira (Latin American Journal of Aquatic Research, 2014)
C obia ( Rachycentron canadum ) is a marine finfish with good potential for mariculture . This study analyzes the effects of probiotic Bacillus spp. on the performance of cobia larvae reared in a recirculating aquaculture system (RAS). Larvae were stocked into two independent RAS for 26 days after hatching. One of the systems (Probiotic treat ment) received the addition of a commercial probiotic consisting of B. subtilis , B. licheniformis and B. pumilus directly into the water and by live feed. Survival, final weight and water quality were not affected by probiotics. Results showed larvae of th e probiotic treatment demonstrated a greater resistance to salinity stress. Immunohistochemical analysis showed a higher expression of CD4 in probiotic treatment. These results suggest that Bacillus spp. probiotics used in RAS have a potential stimulating impact on immune system differentiation and increases salinity stress resistance of cobia larvae.